2014
DOI: 10.25100/cm.v45i4.1640
|View full text |Cite
|
Sign up to set email alerts
|

Global differential expression of genes located in the Down Syndrome Critical Region in normal human brain

Abstract: Background: The information of gene expression obtained from databases, have made possible the extraction and analysis of data related with several molecular processes involving not only in brain homeostasis but its disruption in some neuropathologies; principally in Down syndrome and the Alzheimer disease. Objective: To correlate the levels of transcription of 19 genes located in the Down Syndrome Critical Region (DSCR) with their expression in several substructures of normal human brain. Methods: There we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 27 publications
0
10
0
Order By: Relevance
“…Cognitive function such as working memory is involved in insulin signaling dysfunction and blood glucose levels. It was reported that working memory is linked with T2MD [35][36][37].…”
Section: Shared Crebbp Mapk and Pi3k-akt Pathways Between Ad And T2dmmentioning
confidence: 99%
“…Cognitive function such as working memory is involved in insulin signaling dysfunction and blood glucose levels. It was reported that working memory is linked with T2MD [35][36][37].…”
Section: Shared Crebbp Mapk and Pi3k-akt Pathways Between Ad And T2dmmentioning
confidence: 99%
“…One of them, SOD1 (superoxide dismutase 1), is responsible for maintaining the oxidative balance. The overexpression of SOD1 leads to an imbalance between oxidative factors and antioxidants, which contributes to neuroinflammation and increased Aβ production [112]. Also, the recent studies have shown that polymorphism of β-secretase (BACE-1) has a significant influence on the development of familial AD [113][114][115].…”
Section: Alzheimer's Disease As a Consequence Of Other Diseasesmentioning
confidence: 99%
“…Disruption of mitochondrial processes, especially the mitochondrial respiratory chain, stimulates the production of ROS, which promotes the pathogenesis of AD and neuronal apoptosis. Mitochondrial dysfunction is believed to be directly responsible for cognitive decline because the resulting energy deficits disrupt cholinergic neurotransmission [98,99,112,[116][117][118][119]. Two cohort studies of AD in DS patients are currently recruiting participants (NCT04149197, NCT03901261), and this may shed light on the development of dementia in DS patients.…”
Section: Alzheimer's Disease As a Consequence Of Other Diseasesmentioning
confidence: 99%
“…This terabyte amount data of information is necessary to be analyzed by computational simulation procedures that use bioinformatics analysis tools to get information about the spatial and temporal gene expression. Moreover, the bioinformatics analysis permits to extract information about genes which are expressed in normal and pathological samples of postmortem brains [34,35].…”
Section: As Shown Inmentioning
confidence: 99%